1984
DOI: 10.1063/1.333425
|View full text |Cite
|
Sign up to set email alerts
|

Spin glassiness and ferromagnetism in disordered Ni-Mn (invited)

Abstract: With decreasing Mn concentration near 25 at. %, disordered Ni-Mn alloys are seen to evolve from a characteristic spin-glass behavior, with the magnetic polarizability rapidly increasing, to a magnetic behavior that signifies the onset of ferromagnetic order and the appearance of a spin-glass-like phase at lower temperatures. Moreover, the latter phase is ‘‘mixed’’ in that its equilibrium state (in the fields applied during cooling) manifests a spontaneous ferromagnetic moment, while its magnetization reversals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…The presence of the Cu 3 Au-type superstructure was confirmed in the NiMn alloys with compositions close to this critical content of Mn [1,4]. A mix of ferromagnetic and spin glass behavior was described in the disordered NiMn alloys with the almost critical Mn content at temperatures below 100 K [3] …”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…The presence of the Cu 3 Au-type superstructure was confirmed in the NiMn alloys with compositions close to this critical content of Mn [1,4]. A mix of ferromagnetic and spin glass behavior was described in the disordered NiMn alloys with the almost critical Mn content at temperatures below 100 K [3] …”
Section: Introductionmentioning
confidence: 69%
“…The local moment in the Ni sites is very sensitive to the total moment of the alloys. It can be seen from the extraordinarily low value of m(Ni) in the disordered Ni 75 Mn 25 alloy that is on the verge of an existence of the magnetic state in the NiMn disordered alloys[1][2][3][4]8,9]. However, regardless of the behavior of m(Ni), the significant changes of m(Mn±) under pressure can be considered as the dominant effect in the extraordinary pressure behavior of magnetization of the disordered NiMn alloys.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…The results of the present work clearly demonstrate that the magnetic behavior of the CaNi 1-x Mn x Ge is characterized by the coexistence of magnetic glassy state and FM ordering, which is quite similar to the systems of Ni-Mn, in which FM and SG coexist. 33,34 Such magnetic behavior has not been reported for 111-and 122-type compounds containing MnX 4 (X = Si, Ge) tetrahedrons diluted with "nonmagnetic" T mX 4 units. However, similar glassy ferromagnetism has been found in many ordered and disordered magnetic materials spanning from insulating oxides to metallic compounds, and the origin of such behavior has been always been traced to the presence of FM clusters due to compositional fluctuation or phase separation.…”
Section: B Magnetic Propertiesmentioning
confidence: 91%
“…Metallic ferromagnetic alloys with competing nearest-neighbor interactions tuned by the concentration x show a magnetic phase diagram (T, x) in qualitative agreement with mean-field predictions. Well-known examples are Ni 1−x Mn x [9], Au 1−x Fe x [10], Fe 1−x Al x [11,12], and Fe 1−x Cr x [13] crystalline alloys or amorphous Fe-based alloys [14][15][16][17][18]. A large body of experimental and theoretical studies have revealed the peculiarities of their magnetic behavior.…”
Section: Reentrant Spin Glasses and "Frustrated" Skyrmionsmentioning
confidence: 99%